Study protocol: LIAM Mc trial (Linking In with Advice and supports for Men impacted by Metastatic cancer) - Brendan Noonan; Philip Bredin; Anita M. Cahill; Stephanie Corkery; Katie E. Johnston; Katarina Medved; Anne Marie Cusack; Josephine Hegarty; Mohamad M. Saab; Samantha J. Cushen; Roisin Connolly; Brendan Palmer; et al. (PLoS ONE, 2025)
Background The significant increase in cancer survivorship rates necessitates a comprehensive, multidisciplinary approach to supportive care services. This study seeks to assess the feasibility of introducing a Men’s Health Initiative supportive care intervention program in Ireland. Methods This is a single-arm feasibility study involving a 12-week men’s cancer survivorship programme alongside routine follow-up care in patients with advanced genitourinary malignancies. Men with advanced/metastatic genitourinary cancer (including prostate, kidney, urothelial tract, testicular or penile cancer), are eligible to enrol, with a target of 72 participants over a 2-year period. The intervention programme entails a twice-weekly physiotherapy-led exercise programme, along with dietetics, nursing, and psychosocial components, and regular signposting to additional available services. A Pilot Phase involving analysis of data from the first group of 6 participants to complete the programme is planned, before an Expansion Phase. Assessments will occur at baseline, on completion of the 12-week intervention, and 3 months post-intervention, and will include analyses of exercise/activity levels, body composition, muscle strength, psychological wellbeing, quality of life and resources utilised. The primary endpoints are to determine the feasibility and acceptability of introducing a men’s cancer survivorship intervention programme into routine follow-up care in patients with advanced genitourinary malignancies. Secondary endpoints include impact of the intervention programme on quality of life, cancer-related fatigue, maintenance of weight, changes in body composition and changes in dietary intake and diet quality over the study period, as well as self-care agency and its relationship to quality of life and symptoms experienced. A qualitative process evaluation will be undertaken to explore participants’ experiences, while an economic analysis will examine the healthcare resource utilization and costs associated with the intervention. The trial was peer-reviewed by the Irish Cancer Society. Discussion The programme described in this protocol provides a supportive and safe environment for the introduction of self-care interventions using a small group-based format supported by individualised counselling according to the participant’s identified needs. The development and implementation of future supportive care programmes for men’s cancer survivorship will be guided by the findings of this study. Trial registrartion ClinicalTrials.gov NCT05946993